RAPID MAGNETIC PRINTING OF 3D CELLULAR STRUCTURES USING MAGNETIC CELL BIOINKS - Mishriki, Sarah (My University, 2023)
In this thesis, a rapid magnetic printing technique has been developed for contactless, label-free, and scaffold-free printing of three dimensional (3D) cellular structures in vitro. The biological inks (bioinks) used to form these structures were composed of cells suspended in a liquid medium. Development of this technique was based on exploiting the inherent magnetic susceptibility of cells. Since cells and their liquid medium are diamagnetic (negative magnetic susceptibility), a paramagnetic salt hydrate, gadopentatic acid (Gd-DTPA), was added to the liquid medium to increase its magnetic susceptibility. When a magnetic field was applied, the host fluid containing the paramagnetic salt was towards regions of high magnetic field strength, displacing the cells towards regions towards regions of low magnetic field strength. This rapid printing technique using magnetic cell bioinks was first described using whole blood to form various structures including spherical clusters (spheroids), strips, and three-pointed stars. This demonstration verified the printing technique as a safe and non-toxic method. Subsequent studies were performed using a frequently studied human breast cancer cell line, Michigan Cancer Foundation-7 (MCF-7), to develop a thorough protocol using mammalian cells. Here, the printing method was used to form 3D cellular structures on ultra-low attachment (ULA) and 2.5D cellular structures on tissue-culture-treated (TCT) surfaces. These geometries were produced within 6 hours with high reproducibility. The use of a co-culture on TCT surfaces using MCF-7 and human umbilical vein endothelial cells (HUVECs) and on ULA surfaces using MD Anderson metastatic breast-231 (MDA-MB-231) and embryonic mouse fibroblast (3T3) cells demonstrated the observance of unique cellular interactions and improved printing abilities (accelerated time and improved reproducibly) of the structures printed with magnetic inks, respectively. The use of magnetic cell inks in research and clinical settings can accelerate the development of medical innovations such as drug discovery, personalized medicine, and treatment of disease.
Keywords: Magnetic bioprinting; Rapid magnetic printing